Reconciling work and family : issues and policies in Trinidad and Tobago - Reddock, Rhoda (ILO GenevaCH, 2008)
Provides information on workers' experience of negotiating work and family responsibilities and the implications for gender equality and poverty in Trinidad and Tobago